Prática escritural e produção de espaço em Graciliano Ramos - Tiago de Holanda Padilha Vieira (2022)
This dissertation seeks to analyze ways in which Graciliano Ramos considers writing practice as a producer of space. The corpus consists of five posthumously published books: Linhas Tortas (1962); Viventes das Alagoas (1962); Cartas (1980); Cartas inéditas de Graciliano Ramos a seus tradutores argentinos, Benjamín de Garay e Raúl Navarro (2008); and Garranchos (2012). More precisely, we selected texts that explicitly thematize the act of writing. In addition to the mentioned works, three interviews with Graciliano – two included in Conversas (2014), another in the collection Graciliano Ramos (1977) – and a chronicle included in Cangaços (2014) are used as auxiliary sources. When we analyze how critical studies on the writer’s works present some theoretical treatment of the category of space, two major theoretical-critical lines stand out. Our research adopts the counter-canonical one, according to which the world – that is, what is variably defined as the real world – is not merely given, but it and the act of writing (notably, the literary creation) that thematizes it are mutually determined, so that none of these elements is isolable as a semantic foundation. We explore this view in dialogue with Gilles Deleuze, Félix Guattari, Wolfgang Iser, Cornelius Castoriadis and Jean-Paul Sartre. Some of the selected texts by Graciliano present this same perspective, although the corpus defends different theoretical-critical directions, when characterizing ways in which the act of writing produces space. Therefore, Graciliano does not show a single, totalizing understanding of what writing – and specifically literature – is or should be.